Functional MRI of imprinting memory in awake newborn domestic chicks - Mehdi Behroozi; Elena Lorenzi; Sepideh Tabrik; Martin Tegenthoff; Alessandro Gozzi; Onur Güntürkün; Giorgio Vallortigara (Communications Biology, 2024)
Abstract Filial imprinting, a crucial ethological paradigm, provides insights into the neurobiology of early learning and its long-term impact on behaviour. To date, invasive techniques like autoradiography or lesions have been used to study it, limiting the exploration of whole brain networks. Recent advances in fMRI for avian brains now open new windows to explore bird’s brain functions at the network level. We developed an fMRI technique for awake, newly hatched chicks, capturing BOLD signal changes during imprinting experiments. While early memory acquisition phases are understood, long-term storage and retrieval remain unclear. Our findings identified potential long-term storage of imprinting memories across a neural network, including the hippocampal formation, the medial striatum, the arcopallium, and the prefrontal-like nidopallium caudolaterale. This paradigm opens up new avenues for exploring the broader landscape of learning and memory in neonatal vertebrates, enhancing our understanding of behaviour and brain networks.